The Impact of UK Election Exit Polls on the Foreign Exchange Market and Their Implications For Efficient Markets - Sumpner, Matthew (2020)
This study analyses the effect of UK election exit polls on financial markets; specifically the foreign exchange market. It is the first to investigate in detail the effect exit polls have on the financial markets and does so by utilising event study methodology. High frequency 1-minute tick data, measuring the spot price of the GBP/USD exchange rate, is used to assess the impact the release of the exit poll has on the financial market. Results from this investigation demonstrate that the release of the exit poll can indeed result in abnormal returns being realised in the foreign exchange market. Furthermore, this study identifies Brexit, exit poll unpredictability, and the party predicted to win the largest number of seats, as factors that contribute to the level of abnormal returns we see following the release of the exit poll. Finally, this study judges markets to be more efficient as time has passed due to the increasing use of technology in finance which has facilitated the rise of high frequency trading.